2018
DOI: 10.1021/acscatal.7b04226
|View full text |Cite
|
Sign up to set email alerts
|

Mo- and Fe-Modified Ni(OH)2/NiOOH Nanosheets as Highly Active and Stable Electrocatalysts for Oxygen Evolution Reaction

Abstract: Highly active and stable electrocatalysts for oxygen evolution reaction (OER) are required for industrial hydrogen production. Herein, we report Mo and Fe modification as a synergistic effect to enhance both activity and stability for OER. The Mo-and Fe-modified Ni(OH) 2 /NiOOH nanosheets needs an overpotential of only ∼280 mV to achieve a current density of 100 mA cm −2 and shows no evidence of degradation after 50 h at such high current density, outperforming all OER catalysts reported to date. This work may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
151
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(157 citation statements)
references
References 46 publications
(71 reference statements)
6
151
0
Order By: Relevance
“…The effect of oxygen and Ni + x functionalization on the optical absorption properties of g‐C 3 N 4 was probed by UV/Vis absorption spectroscopy (Figure a). The absorption edge of g‐C 3 N 4 was approximately 421 nm (2.94 eV), which was slightly larger than that reported for bulk g‐C 3 N 4 (2.7 eV) . This increase in bandgap further confirmed that g‐C 3 N 4 had a nanosheet morphology, as the bandgap of nanosheets increases in comparison with the bulk because of the quantum confinement effect .…”
Section: Resultssupporting
confidence: 73%
“…The effect of oxygen and Ni + x functionalization on the optical absorption properties of g‐C 3 N 4 was probed by UV/Vis absorption spectroscopy (Figure a). The absorption edge of g‐C 3 N 4 was approximately 421 nm (2.94 eV), which was slightly larger than that reported for bulk g‐C 3 N 4 (2.7 eV) . This increase in bandgap further confirmed that g‐C 3 N 4 had a nanosheet morphology, as the bandgap of nanosheets increases in comparison with the bulk because of the quantum confinement effect .…”
Section: Resultssupporting
confidence: 73%
“…An extraordinarily low onset potential is calculated as 1.425 V (η 10 ) from VOOH‐Fe sample, which was significantly lower than the other four electrodes (VOOH‐5Fe: 1.472 V, VOOH‐1Fe: 1.477 V, VOOH‐10Fe: 1.479 V, and VOOH‐0Fe: 1.484 V). To the best of our knowledge, 195 mV overpotential versus 10 mA cm −2 is the best value reported for V or Fe (oxy)hydroxides and transcends many of the previously reported nonprecious metal OER catalysts, including Fe 0.5 V 0.5 OOH, Fe 0.33 Co 0.67 OOH, MoFe:Ni(OH) 2 /NiOOH, Co‐V hydr(oxy)oxide, F‐CoOOH/NF, CoS x /N‐doped graphene, etc. (Table S3, Supporting Information).…”
Section: Resultssupporting
confidence: 68%
“…However, despite these advantages, high rates require electrocatalysts with rich active sites in which electrons involving in the formation of metal‐oxygen bonds relating to oxygen evolution intermediates can be more stabilized. Moreover, the other factor limiting the OER activity is a charge transfer rate from oxygen evolution intermediates to the accessible reaction sites of a catalyst, so that using high‐valence metals could be a good choice to facilitate charge transfer since their valence states could be easily modulated by accepting electrons from oxygen evolution intermediates or donating electrons to electrodes. Another challenge is in that the surface reaction sites of a catalyst could be degraded due to the slow charge transfer under oxidative OER conditions .…”
mentioning
confidence: 99%
“…Another challenge is in that the surface reaction sites of a catalyst could be degraded due to the slow charge transfer under oxidative OER conditions . Density functional theory (DFT) calculations proposed that Fe‐ and Mo‐doping on NiOOH could give the increased charge transfer for high activity in OER. These allow one to hypothesize that using the reduced metallic states of nickel and iron metals on conjugation with high‐valence modulating metals as catalytic reaction sites is a great choice for high rate and fast charge transfer in OER.…”
mentioning
confidence: 99%
See 1 more Smart Citation